2014
DOI: 10.1007/s40620-014-0154-0
|View full text |Cite
|
Sign up to set email alerts
|

High uric acid level is a risk factor for progression of IgA nephropathy with chronic kidney disease stage G3a

Abstract: H-UA induced global glomerular sclerosis and accelerated the progression of IgAN in CKD stage G3a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…However, most of these studies have not been adjusted for the renal pathological injuries and treatments. A few recent studies drew inconsistent results [19,20]. Our study also indicated that higher levels of SUA were significantly associated with a higher risk of developing primary outcome or kidney failure, even after adjustment for the confounder factors.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…However, most of these studies have not been adjusted for the renal pathological injuries and treatments. A few recent studies drew inconsistent results [19,20]. Our study also indicated that higher levels of SUA were significantly associated with a higher risk of developing primary outcome or kidney failure, even after adjustment for the confounder factors.…”
Section: Discussionmentioning
confidence: 46%
“…In agreement with the present study, the risk of developing outcome was significantly increased (HR 1.79, 95% CI 1.29-2.49) in the IgAN patients with hyperuricemia as compared with those with normal SUA levels by combining 3 studies enrolling a total of 1,591 patients [31][32][33]. Every 1 mg/24 h higher SUA was associated with a 16% higher risk of developing outcome (HR 1.30, 95% CI 1.13-1.49) by combining the other 2 studies enrolling a total of 1,623 patients [15,20] (online suppl. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some studies have confirmed that the change in uric acid, citric acid, and creatinine are closely related to antioxidant system and energy metabolism, as well as the biomarker of kidney function. [42][43][44] In this study, the abovementioned biomarker of liver and kidney dysfunction in group PQ2 was alleviated compared with group P (p < 0.05). This result may be explained by the potency of quercetin protective effect against kidney and liver failure by scavenging free radical, enhancing the activity of antioxidant enzymes, downregulating the expression of the fibrotic marker MMP-9, and reducing the peroxidative marker malonaldehyde and inflammatory marker nitric oxide.…”
Section: Discussionmentioning
confidence: 48%